A Prospective Study of Ligature Mark in Deaths Due to Hanging - Karthik SK; Mohana Velu J; Jayaprakash G (Indian Journal of Forensic Medicine & Toxicology, 2021)
Hanging is one of the ten leading causes of death in the world accounting for more than a million deaths annually. The hanging deaths are one of the most important asphyxial types of death which are encountered in day to day life by forensic pathologists. Ligature mark in the neck is the principal external sign in hanging depending on body suspension from ligature point. This prospective study was conducted at the Department of Forensic Medicine, Dr.B.R.Ambedkar Medical College, Bengaluru between January 2018 to December 2018 to assess the information provided by a ligature mark in deaths due to hanging. We found that typical hanging is seen in 50 cases and atypical hanging in 225 cases. Partial hanging is seen in 73.09% deaths and complete hanging in 26.9% deaths. Ligature mark was obliquely placed in 91.3% cases and was found to be running above thyroid cartilage in 80.7% cases. Single ligature mark with a breadth of 1-2cms is observed in the maximum number of cases. In 93% of the incidents, ligature mark showed discontinuity. The colour of ligature mark was reddish-brown in 46.9% cases